2001
DOI: 10.1007/s002590100578
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution and dosimetry of 99mTc-BTAP-annexin-V in humans

Abstract: The purpose of this study was to determine the biodistribution and the associated radiation dose of technetium-99m 4,5-bis(thioacetamido)pentanoyl-annexin-V (99mTc-Apomate), a tracer proposed for the study of apoptosis. Eight patients (including two females) with normal kidney and liver functions were included in the study. An activity of 580 +/- 90 MBq of 99mTc-Apomate was injected intravenously, immediately followed by a dynamic study of 30 frames of 1 min each. At about 1 h, 4 h and 20 h p.i., whole-body sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
71
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 9 publications
0
71
0
1
Order By: Relevance
“…The biodistribution study of 18 F-ML-10, a small-molecule apoptotic tracer, demonstrated a distinct pattern of uptake in the testes (27). However, the biodistribution studies of annexin-Vbased radiotracers ( 99m Tc-annexin-V, 99m Tc-hydrazino nicotinate [HYNIC]-annexin-V, and 99m Tc-4, 5-bis [thioacetoamide] pentanoyl [BTAP]-annexin-V) did not show increased uptake in the testes, with the absorbed dose in the testes ranging from 0.005 to 0.015 mGy/MBq (28)(29)(30). This dose is comparable to the absorbed testes dose observed with 18 F-ICMT-11 (0.007 mGy/MBq).…”
Section: Discussionmentioning
confidence: 99%
“…The biodistribution study of 18 F-ML-10, a small-molecule apoptotic tracer, demonstrated a distinct pattern of uptake in the testes (27). However, the biodistribution studies of annexin-Vbased radiotracers ( 99m Tc-annexin-V, 99m Tc-hydrazino nicotinate [HYNIC]-annexin-V, and 99m Tc-4, 5-bis [thioacetoamide] pentanoyl [BTAP]-annexin-V) did not show increased uptake in the testes, with the absorbed dose in the testes ranging from 0.005 to 0.015 mGy/MBq (28)(29)(30). This dose is comparable to the absorbed testes dose observed with 18 F-ICMT-11 (0.007 mGy/MBq).…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15] In addition, investigation of the biodistribution and dosimetry of various forms of radiolabeled annexin in human subjects has demonstrated the Circulation Journal Vol.71, July 2007 safety of this agent, as well as the efficacy of imaging for the detection of acute myocardial infarction (MI) and cardiac transplant rejection. [16][17][18][19][20] In patients with MI, there is intense localization of 99m TcAnnexin-V in the infarct region, both in patients with and those without reperfusion, 18,21 which suggests that a considerable number of cells in the infarct zone die by apoptosis. 22,23 Although the most effective method of limiting the zone of injury in areas of markedly decreased perfusion is restoration of blood flow, experimental studies have demonstrated that reperfusion is a major stimulus for apoptosis in previously ischemic tissue, especially in nonsalvageable cells.…”
mentioning
confidence: 99%
“…[16][17][18][19][20] In patients with MI, there is intense localization of 99m TcAnnexin-V in the infarct region, both in patients with and those without reperfusion, 18,21 which suggests that a considerable number of cells in the infarct zone die by apoptosis. 22,23 Although the most effective method of limiting the zone of injury in areas of markedly decreased perfusion is restoration of blood flow, experimental studies have demonstrated that reperfusion is a major stimulus for apoptosis in previously ischemic tissue, especially in nonsalvageable cells.…”
mentioning
confidence: 99%
“…Выявление апоптотических клеток с помощью ОФЭКТ основано на визуализации молекул анионного липида фосфатидилсерина (которые экспонированы на поверхности апоптотических, но не интактных клеток) с помощью радиофармпрепарата, содержащего белок аннексин V. В 1998 г. были получены первые аннексиновые зонды, меченные 99m Tc [57]. Результаты клинических испытаний указанных радиофармпрепаратов свидетельствуют о хорошей переносимости процедуры их внутривенного введения и отсутствии побочных эффектов [58,59]. Период полувыведения из организма 99m Tc-аннексина V составляет 62±13 ч. Проведена вторая фаза клинических испытаний 99m Tc-HYNIC-аннексина V с целью визуализации апоптоза у 16 больных немелкоклеточным раком лёгкого после начала лечения комбинацией цисплатины и гемцитабина [60].…”
Section: методы визуализации апоптотических клеток In Vivounclassified